Trust is good, control is better: a review on monitoring and characterization techniques for flow battery electrolytes. Issue 7 (26th March 2021) - Nolte, Oliver; Volodin, Ivan A.; Stolze, Christian; Hager, Martin D.; Schubert, Ulrich S.
Abstract : This review article summarizes the state-of-the-art techniques for the characterization and monitoring of flow battery electrolytes highlighting in particular the importance of the electrolyte state-of-charge and state-of-health assessment. Abstract : Flow batteries (FBs) currently are one of the most promising large-scale energy storage technologies for energy grids with a large share of renewable electricity generation. Among the main technological challenges for the economic operation of a large-scale battery technology is its calendar lifetime, which ideally has to cover a few decades without significant loss of performance. This requirement can only be met if the key parameters representing the performance losses of the system are continuously monitored and optimized during the operation. Nearly all performance parameters of a FB are related to the two electrolytes as the electrochemical storage media and we therefore focus on them in this review. We first survey the literature on the available characterization methods for the key FB electrolyte parameters. Based on these, we comprehensively review the currently available approaches for assessing the most important electrolyte state variables: the state-of-charge (SOC) and the state-of-health (SOH). We furthermore discuss how monitoring and operation strategies are commonly implemented as online tools to optimize the electrolyte performance and recover lost battery capacity as well as how their automation is realized via battery management systems (BMSs). Our key findings on the current state of this research field are finally highlighted and the potential for further progress is identified.